Impactos ambientais e efeitos à saúde humana, causados pela contaminação de mercúrio na Região Amazônica: uma revisão sistemática - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
Mercury is considered one of the most toxic metals hazardous to the environment and human health due to its high toxicity and its mobility in different ecosystems. From this, the research proposes to identify through a systematic review of the literature the main problems caused by the dumping of mercury, emphasizing the health of the Amazon population, and the damage caused to the environment and animals. The objective of the study is to present a systematic review of the literature on diseases and environmental impacts caused by mercury. The research consists of a systematic review of the literature on the subject. The bibliographical research was carried out from news, articles, monographs and theses and was carried out in the databases: SciELO, BVS (Virtual Health Library), Google Scholar and Portal of Capes journal, published between 2010 and 2023. The following keywords were searched: mercury, contamination, health and Amazon, as the post search, the materials were selected according to the objective of the study. For the preparation of the systematic review, 10 articles were selected. Among the studies, we highlight results pointing to mercury contamination related to the practice of deforestation; contamination by levels of Hg accumulated in fish and populations in the Amazon region; contamination with the mines and the consumption of contaminated fish as responsible for mercury contamination in Amazonian regions. It is also noteworthy that the metal mercury in the mines, causes drastic effects to vulnerable populations and the surrounding environment, and can culminate in serious damage to health, environment.
Keywords: Bioacumulação; Mercúrio; Saúde; CNPQ:: Ciências Biológicas